Tuberculosis In paediatric kidney transplant recipients a single centre experience - Makanda-Charambira, Privilage (Department of Paediatrics and Child Health, 2022)
Background: Tuberculosis remains a major challenge in transplantation particularly in endemic countries. The incidence, clinical manifestations, and optimal investigations for TB specifically in the paediatric post-transplant population have not yet been adequately studied. This study aims to describe the incidence, clinical presentation and outcomes of tuberculosis in paediatric kidney transplant recipients and to assess the impact of Isoniazid prophylaxis. Methods: Single-centre retrospective descriptive analysis of children who received kidney transplants from 1995-2019. The cohort was stratified according to receipt of isoniazid prophylaxis which began in 2005. Results: 212 children received a kidney transplant during the study period. Median age at transplantation was 11.2 years (IQR: 2.2 - 17.9) and 56% were males. Tuberculosis was diagnosed in 20 (9%) children, with almost two thirds (n=12) occurring within the first year post-transplant. The main presenting symptoms included fever (n=13/20), weight loss (n=12/20) and cough (n=10/20). Tuberculin skin test was positive in four of 20 children. Coinfection with Ebstein Barr virus, Cytomegalovirus or Staphylococcus was found in five children. Due to interactions an up to three fold increase in calcineurin inhibitor dose was required to maintain therapeutic blood levels. Isoniazid prophylaxis was protective against development of tuberculosis (p=0.04). ) and was associated with fewer infections within the first year of transplantation although this was not statistically significant (p = 0.3). Gender, age and type of allograft were not significant risk factors for developing tuberculosis. All the tuberculosis infections were successfully treated. There was graft and patient survival of 100%. Conclusion: Kidney transplant recipients have a high risk of tuberculosis. Diagnosis remains a challenge. Frequent and meticulous monitoring of immunosuppression drug levels during treatment of TB is required to avoid loss of patient or graft. Isoniazid prophylaxis protects against development of TB in this population. (HREC 463/2020)